A Numerical Simulation of a Fog Event in the Sichuan Basin, China: The Sensitivity to Terrain Elevations - Ling-Meng Gu; Xin-Min Zeng; Cong-Min Li; Ning Wang; Shuai-Bing Shao; Irfan Ullah (Atmosphere)
In this paper, we utilize the Advanced Research version of the Weather Research and Forecasting model (ARWv4) to explore how the fog is affected by the basin’s topography during a radiation fog event in the Sichuan Basin in December 2016 by setting up three sets of terrain tests. The simulation results demonstrate that the fog area in the expanded basin terrain emerges 40 min earlier than in the original topography control test (CTL), with the fog area extent marginally reduced. Conversely, the fog area in the reduced basin terrain emerges one hour earlier than in the CTL, with the fog area extent increased by 133.5%. Basin topography is an essential factor influencing the humidity, temperature, and dynamical fields. The expansion of basin topography was shown to be unfavorable for water vapor convergence. Moreover, the area exhibiting relative humidity levels exceeding 95% at the peak of the fog intensity was smaller than that observed in CTL. The impact of radiative cooling was diminished, and the thickness and intensity of the inversion layer were reduced compared to CTL. In addition, the wind speed in the marginal area exceeded 5 m s−1, and the fog formation was observed only in the central portion of the basin, where wind speeds ranged from 0 to 3 m s−1. In contrast, the change in the topography of the narrowed basin resulted in the opposite phenomenon overall. This work emphasizes the importance of basin topography in forming and developing the fog in the Sichuan Basin.